1994
DOI: 10.1002/pola.1994.080321511
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and polymerization of propenyl ether analogues

Abstract: SYNOPSISA series of aromatic monomers bearing cationically polymerizable propenyl groups were prepared and characterized using the readily available starting materials: isoeugenol and o-ally1 phenol. Monomers with both propenyl and vinyl ether functional groups were also synthesized by the reaction of these starting materials with chloroethyl vinyl ether. The reactivity of the resulting monomers in photoinitiated cationic polymerization was studied using differential scanning photocalorimetry and photogel poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Lastly, the 1,2 substitution about the double bond in maleate esters results in a greater steric hindrance than in acrylate monomers that impedes the approach of the comonomer during the photopolymerization reaction. It is interesting to note that when the photoinitiated free radical alternating copolymerization of DMM with the more sterically hindered 1,2‐ethylene glycol di‐1‐propenyl ether and 1,10‐decanediol di‐1‐propenyl ether (mixtures of cis and trans isomers)28 was attempted under the same conditions as described above, only very sluggish copolymerizations were observed in both cases. …”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the 1,2 substitution about the double bond in maleate esters results in a greater steric hindrance than in acrylate monomers that impedes the approach of the comonomer during the photopolymerization reaction. It is interesting to note that when the photoinitiated free radical alternating copolymerization of DMM with the more sterically hindered 1,2‐ethylene glycol di‐1‐propenyl ether and 1,10‐decanediol di‐1‐propenyl ether (mixtures of cis and trans isomers)28 was attempted under the same conditions as described above, only very sluggish copolymerizations were observed in both cases. …”
Section: Resultsmentioning
confidence: 99%
“…Owing to the high reactivity of the monomers investigated in this study, we have elected to monitor the course of their cationic photopolymerizations using real-time infrared spectroscopy (RTIR). We , and others have reported the use of this technique for the determination of the rates of very rapid photopolymerizations which are completed on a time scale of a few seconds. This technique consists of following in real time the disappearance of specific infrared bands characteristic of the functional groups undergoing polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have observed that such reactions predominate during the attempted cationic photopolymerizations of alkoxystyrene and alkoxy-␣-methylstyrene monomers. 10,11,12,13 A variety of branched and cyclic repeating units are generated during the polymerization of these monomers, and molecular weights are typically low due to chain transfer reactions. The Friedel-Crafts alkylation reaction proceeds most readily in aromatic compounds substituted by electrondonating groups.…”
Section: Anisole Probe Experimentsmentioning
confidence: 99%
“…13 C-NMR (in CDCl 3 ) of PhPE polymerized in the presence of anisole (1 : 1 molar ratio) using IOC10SbF 6 .…”
mentioning
confidence: 99%